Filogeografia comparada e preditiva na divisão leste-oeste do Cerrado: teste de divergência simultânea e identificação de características preditoras de quebra filogeográfica - Silva, Luana Maria Deoclécio da (Universidade Federal de São Carlos, 2022)
The Cerrado is a vast savanna formation in central Brazil currently included in the list of the main global hotspots for biodiversity conservation. Despite the recognition of its biological relevance, the biogeographic processes that shaped the diversification of its biota at different taxonomic levels are still poorly understood. A relatively common pattern inferred in different Cerrado species is a phylogeographic break in the Brazilian Central Plateau, separating populations of different animal and plant species in an east-west direction. In this work, we combine comparative phylogeography with the predictive framework of machine learning to investigate the existence of synchronous events between species/population pairs that show the reported phylogeographic pattern and identify predictive variables of this divergence. The east-west phylogeographic break was determined through the construction of phylogenetic trees and when the authors of the articles reported the east-west division. We used Bayesian inference of shared evolutionary events to estimate the timing and synchronicity of divergence in eight taxa pairs comprising plants, arthropods, lizards, and frogs. Finally, we build a random forest statistical model using biotic and abiotic information to identify the best predictors of the phylogeographic structure. We identified that spatial congruence is associated with temporal synchrony in plants, mainly related to Pleistocene climatic events that preceded the Last Glacial Maximum. We identified multiple divergence pulses within animals that coincide with Neogene geological events and Quaternary climatic oscillations. Our statistical model predicted that biotic variables related to dispersal ability, gene flow, and habitat preference played a crucial role in structuring the east-west break of the central Cerrado lineages, consistent with the relative contributions of extrinsic and intrinsic forces that drive the responses of organisms.
Comparative and predictive phylogeography in the east-west division of the Cerrado: test of simultaneous divergence and identification of predictive characteristics of phylogeographic break
Keywords: Biogeografia; Filogeografia comparada; Variação genética; Cerrado; Aprendizado de máquina; Inferência bayesiana; CIENCIAS BIOLOGICAS::GENETICA::GENETICA MOLECULAR E DE MICROORGANISMOS